Analysis of Trends in Publications Strength Based Counseling in Global and Indonesia - Amalianita, Berru; Harahap, Nur Hasanah; Annisa, Dona Fitri; Alawiyah, Tuti (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2024)
This literature study investigates the development of strengths-based counseling publications. This research highlights scientific developments, authors, and countries that are developing in family-based counseling research. The findings reveal that the development of strengths-based counseling publications began after 2000, marked by a large number of publications. 2022-2024 will be the highest year for strength-based counseling publications in article form. America has 131 publications, while Indonesia has 48 publications. Medical science has become the highest publication in the context of strengths-based counseling. The use of Strengths-Based Counseling in Indonesia and on a global scale shows optimistic progress. School counselors can effectively provide services to clients by utilizing a Strengths-Based Counseling approach, which can contribute to improved psychological well-being by leveraging individual strengths and community supports